2018
DOI: 10.1590/0037-8682-0365-2016
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety disorders among patients with human T-cell lymphotropic virus type-1: a cross-sectional study with a comparison group

Abstract: Symptomatic and asymptomatic patients with HTLV-1 experienced more anxiety and depression than uninfected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Our findings showing no associations between HTLV-1 and cognitive function differ from several other previous reports that have shown associations between HTLV-1 and cognitive function and depression in comparisons of HAM/TSP with healthy controls and with asymptomatic HTLV-1 and healthy controls [10,11,19,21]. Several factors could plausibly account for the differences between our findings and previous reports that found associations between HTLV-1 and cognitive function and between HTLV-1 and depression.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Our findings showing no associations between HTLV-1 and cognitive function differ from several other previous reports that have shown associations between HTLV-1 and cognitive function and depression in comparisons of HAM/TSP with healthy controls and with asymptomatic HTLV-1 and healthy controls [10,11,19,21]. Several factors could plausibly account for the differences between our findings and previous reports that found associations between HTLV-1 and cognitive function and between HTLV-1 and depression.…”
Section: Discussioncontrasting
confidence: 98%
“…In addition to its association with worse cognitive function, HTLV-1 also has been associated with depression and anxiety. A cross-sectional study from Brazil that investigated 20 patients with HAM/TSP, 38 asymptomatic HTLV-1 patients, and 340 healthy controls found that both HAM/TSP and asymptomatic HTLV-1 were associated with depression and anxiety [11], although the analyses in this study were not adjusted for covariates that could potentially influence the association between HTLV-1 and either depression or anxiety. Another study from Brazil compared levels of depression and anxiety between 63 patients with HAM/TSP and 67 patients with asymptomatic HTLV-1, finding that the patients with HAM/TSP had more depression and anxiety than the asymptomatic HTLV-1 group.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, studies have shown that HTLV-1 seropositive individuals may present with a broad range of clinical manifestations, including inflammatory syndromes (uveitis, thyroiditis, and alveolitis), neurological symptoms not explained by myelopathy (polyneuropathy, myositis, dysautonomia), and opportunistic co-infections (strongyloidiasis, tuberculosis, and aspergillosis) 7 . Some studies have even shown that HTLV-1 infection may be associated with clinical depression and nutritional deficiencies 16,17 . However, the vast majority of patients that are HTLV-1 positive remain asymptomatic, and the precise mechanisms underlying the development of symptoms in a subgroup of patients remain to be determined 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Screening for depression during pregnancy may be useful in evaluating both aspects [100]. Rocha-Filho et al showed that both symptomatic and asymptomatic patients with HTLV-1 experienced more anxiety and depression than those experienced by uninfected patients [101]. Thus, it is believed that carrier mothers may have similar experiences.…”
Section: Prevention Of Mtct By Nutritional Regimensmentioning
confidence: 99%